Improving the effectiveness of the child protection system: A review of literature - Schrader McMillan, S; Barlow, J (Early Intervention Foundation, 2017)
The objective of this rapid review of the literature was to identify both known and emerging/innovative systems and practices that have been shown to improve outcomes for children (i) who have experienced abuse and neglect or (ii) are clearly identified as being at risk of abuse. The objective of the review was also to identify effective programmes, as well as evidence regarding effective methods of assessment and engagement, and practitioner training, working and management. Where possible the analysis aimed to identify the reliability of the evidence, scale of impact, and evidence of potential to reduce costs or mitigate the need for increased spending on children’s services and other parts of the child protection system.